2015
DOI: 10.1136/bjsports-2015-094691
|View full text |Cite
|
Sign up to set email alerts
|

Return to sport after open and microdiscectomy surgery versus conservative treatment for lumbar disc herniation: a systematic review with meta-analysis

Abstract: Background Lumbar disc herniation has a prevalence of up to 58% in the athletic population. Lumbar discectomy is a common surgical procedure to alleviate pain and disability in athletes. We systematically reviewed the current clinical evidence regarding athlete return to sport (RTS) following lumbar discectomy compared to conservative treatment. Methods A computer-assisted literature search of MEDLINE, CINAHL, Web of Science, PEDro, OVID and PubMed databases (from inception to August 2015) was utilised using k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…However, the extant systematic reviews primarily focused on one treatment type or one type of lumbar disc herniation. A total of four published systematic reviews 1013 that compared surgery with non-operative treatments for lumbar disc herniation are available. One of these articles, 12 which was published in 2007, is an updated Cochrane review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the extant systematic reviews primarily focused on one treatment type or one type of lumbar disc herniation. A total of four published systematic reviews 1013 that compared surgery with non-operative treatments for lumbar disc herniation are available. One of these articles, 12 which was published in 2007, is an updated Cochrane review.…”
Section: Discussionmentioning
confidence: 99%
“…The said review only provided a descriptive analysis without meta-analysis. The last article 10 focuses on returning to sports after open and microdiscectomy surgery versus conservative treatment for lumbar disc herniation. The current systematic review and meta-analysis combined all of the evidence from many relevant studies that evaluated the different forms of surgical or non-operative treatment into one review to assess the overall effects of surgical versus non-operative treatment on patients with lumbar disc herniation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that at 3, 6, and 12 months post-surgery, 50%, 72%, and 84% of patients were eligible to return to play, respectively [64]. However, it was found that only 38 to 65% of players who underwent surgical treatment for a lumbar disc herniation were able to return to the same level of play as prior to the injury [65]. Additionally, one meta-analysis has noted that the age at which a player undergoes surgery is an important factor in determining career length post-operatively, but the relationship is sport-dependent [65].…”
Section: Main Textmentioning
confidence: 99%
“…However, it was found that only 38 to 65% of players who underwent surgical treatment for a lumbar disc herniation were able to return to the same level of play as prior to the injury [65]. Additionally, one meta-analysis has noted that the age at which a player undergoes surgery is an important factor in determining career length post-operatively, but the relationship is sport-dependent [65]. In the National Hockey League, regardless of surgical versus non-surgical treatment, players with a lumbar disc herniation played in 56.2 games per season pre-injury versus 39.0 games per season post-injury [66].…”
Section: Main Textmentioning
confidence: 99%